(untitled) (The Research of Medical Science Review, 2025)
The Lydia Hall’s theory of Core, Care and Cure Model focuses on the nurses’ role in holistic patient care. It applies primarily in acute care settings for patients above 16 years, it focuses on therapeutic communication and patience centered care. A clinical scenario involving patients with severe chest pain determines the model’s application. The nurse addressed anxiety (Core), provided immediate care (Cure) and ensured a supportive environment (Care). However, a gap in discharge education revealed challenges in complementation. Hall’s model highlights nurses’ role in advocacy, education and holistic healing, while effective in acute care, it focuses on prevention and community health. It remains a valuable framework for improving patient recovery, nursing efficiency and patient trust.